Modified laser-fired contact process for efficient PERC solar cells - Choi, Jae Myeong; Jung, Beomsic; Park, Jong-Keuk; Kim, Won Mok; Lee, Doh-Kwon; Jeong, Jeung-hyun; Lee, Taek Sung; Cho, Jea-Young; Ju, Byeong-Kwon; Kim, Inho (WILEY, 2019)
A laser-fired contact (LFC) process is one of the techniques for making local electrical contacts at the rear side of passivated emitter and rear cell (PERC) solar cells. In the LFC process, opening of the passivated dielectric layers and alloying of Si and Al need to be made in a single step laser process. For this reason, the LFC process is accompanied by the loss of Al and the laser damage to the Si wafer. In this study, we present a novel multistep LFC process combining the conventional LFC and laser-induced forward transfer (LIFT) processes. The modified LFC scheme we proposed consists of three steps: (a) opening of the passivation layers and partial alloying of Al-Si, (b) additional deposition of Al on the local contact holes, and (c) post laser firing of the transferred Al. Applying the modified LFC process to the PERC cells of 1.0 cm(2) of area, we demonstrate the effective recombination velocity of the laser-processed wafers can be remarkably reduced while maintaining the low contact resistance. The best of the PERC solar cell fabricated by the modified LFC process exhibited an efficiency of 19.5% while the conventional LFC-PERC cell showed 18.6%. The efficiency gains of the modified LFC-PERC cells was largely contributed by the enhanced open circuit voltage (V-oc) and fill factor (FF).
Keywords: PASSIVATED EMITTER; RECOMBINATION; OPTIMIZATION